1993
DOI: 10.1038/bjc.1993.130
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunolocalisation in breast cancer using the gene product of c-erbB2 as the target antigen

Abstract: Summary Lymph node status is still the single most important prognostic factor in breast cancer. Axillary surgery remains the only reliable means of providing this information. This pilot study evaluates using a highly specific radiolabelled monoclonal antibody to provide equivalent infornation by a non-invasive technique.After optimisation of labelling conditions, our first antibody, ICR12 (against the gene product of c-erbB-2) was evaluated in a mouse model system. Twenty-four hours post i.v. injection the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Tumor uptake of ICR12 was further increased, to 20 %ID/g, with residualizing isotopes (28,29). Similar to what we observed in the present study, tumor uptake of ICR12 was not influenced by the protein dose, but the T/B ratio decreased with an increasing amount of protein (30).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Tumor uptake of ICR12 was further increased, to 20 %ID/g, with residualizing isotopes (28,29). Similar to what we observed in the present study, tumor uptake of ICR12 was not influenced by the protein dose, but the T/B ratio decreased with an increasing amount of protein (30).…”
Section: Discussionsupporting
confidence: 80%
“…In the early 1990s, the rat antibody 99m Tc-ICR12 was administered to 8 breast cancer patients. Tomographic images were obtained at 24 h. The study indicated that 99m Tc-ICR12 could be used for the imaging of HER2/neu overexpression (29), but no further clinical results with this rodent antibody have been published. In a preliminary report, Behr et al suggested that 111 In-trastuzumab could predict the therapeutic efficacy of trastuzumab in 20 patients with HER2/neu-overexpressing metastatic breast cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…This SPECT study suggested that 99m Tc‐ICR12 could be used for the imaging of HER2‐positive disease, although no further clinical results involving this antibody have been made available. 23 Currently, clinical studies with 111 In‐ and 64 Cu‐trastuzumab and with 68 Ga‐trastuzumab F(ab′) 2 fragments are at the stage of patient recruitment. 24 , 25 , 26 These studies will give insight into the possibility of using shorter‐lived isotopes (such as 64 Cu) for imaging with intact antibodies and will provide the first clinical results with the smaller HER2‐directed F(ab′) 2 fragments.…”
Section: Discussionmentioning
confidence: 99%
“…These have shown the ability to image tumors in experimental animals and in humans [90,91]. The therapeutic application of radiolabelled antibodies to this and other types of cancer may depend on the attachment of isotopes of sufficient specific activity and suitable decay pathlength.…”
Section: Novel Approaches To Her2-antibody-based Therapymentioning
confidence: 99%